Dividend Policy and Economic Variable to Stock Price Volatility: Comparison of Indonesia and Malaysia - Harlina, Vega Rut; Khoiruddin, Moh. (Universitas Negeri Semarang, 2018)
This research aims to examine the effect of dividend policy, micro variables, and macroeconomic on stock price volatility. The population in this research are companies in the financial sector listed at Indonesia Stock Exchange and Malaysia Stock Exchange in 2016-2017. A number of samples that used is 58 companies for Indonesia and 28 companies for Malaysia with purposive sampling method. Dividend policy is proxied by EPS, the micro variable is proxied by GA and EV, and the macro variable is proxied by exchange rates and interest rates. The analytical method used is CEM and REM with programs Eviews 9. This research concludes that in Indonesia EPS, exchange rates and interest rates have an effect on SPV. While in Malaysia, only EPS and exchange rates have an effect on SPV.